Penguatan Literasi Keuangan Sebagai Upaya Meningkatkan Kemandirian Finansial Masyarakat di Desa Cempaka Kecamatan Bumijawa - Mirza Anindya Pangestika; Fatkhuri Fatkhuri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Limited financial literacy within the community affects the effectiveness of personal financial management in daily life. Low levels of financial literacy are one of the key factors influencing an individual’s ability to manage finances effectively. Many people are not yet accustomed to recording financial transactions, preparing budgets, or understanding the importance of emergency funds and basic investments. The training provided in this Community Service Program (Pengabdian kepada Masyarakat) was designed to enhance the capacity of the residents of Cempaka Village, Bumijawa District, to manage their finances in a more planned, efficient, and sustainable manner. The methods used in this program included counseling sessions, interactive training, budgeting simulations, and practical exercises in simple financial recording. The participants consisted of 25 individuals, including homemakers, informal workers, and micro, small, and medium enterprise (MSME) actors. Program evaluation was conducted by comparing pre-test and post-test results to identify improvements in participants’ knowledge of financial literacy concepts. The results showed a significant increase in participants’ understanding, with an average improvement of 38%. Participants also demonstrated enhanced abilities in financial record-keeping, budgeting, understanding healthy debt management, preparing emergency funds, and recognizing basic investment instruments. This program had a positive impact on increasing community awareness in managing finances more systematically, thereby supporting the development of financial independence in the community